2019
DOI: 10.1111/jfpe.12988
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of photoactivated curcumin to decontaminate food surfaces under blue light emitting diode

Abstract: The efficacy of photoactivated curcumin in decontaminating food surfaces using a 465 nm light emitting diode (LED) light source was investigated. Under studied conditions, LED illumination alone had negligible antibacterial effects while photoactivated curcumin exhibited strong bactericidal activities against Escherichia coli. Minimum inhibitory concentration of photosensitized curcumin against E. coli on nutrient agar surface at a concentration of 1.5 × 105 cfu/cm2 was estimated to be 1.60 × 10−3 M, combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 59 publications
0
24
1
Order By: Relevance
“…They observed that the aPDI were able to eliminate a 4 log CFU/cm 2 of bacterial population. The results of these studies showed that no negative effects were observed in the food matrices [22,44].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…They observed that the aPDI were able to eliminate a 4 log CFU/cm 2 of bacterial population. The results of these studies showed that no negative effects were observed in the food matrices [22,44].…”
Section: Introductionmentioning
confidence: 90%
“…The authors observed a reduction in E. coli population, as well in the activity of the enzymes polyphenol oxidase and peroxidase. Aurum and Nguyen [44] achieved a 2 log inactivation of E. coli on grapes treated with curcumin at 1.6 µM. The grapes were immersed in curcumin solutions containing the inoculum for 60 min and the samples were afterwards irradiated with a blue LED light (465-470 nm).…”
Section: Introductionmentioning
confidence: 99%
“…The results are supported by refractometer analysis of TSS which showed a 9% increase (p < 0.05) in photosensitized fruits compared to the control (Table 1). Aurum and Nguyen (2019) reported an increase in TSS in grapes treated with curcumin-based photosensitization at a light dose of 36.3 J/cm 2 up to 4 days of storage at 37°C. This increase could be caused by dehydration (Valverde et al 2005) and activity of hydrolytic enzymes (Nabifarkhani et al 2015).…”
Section: Sugar Contentmentioning
confidence: 97%
“…For instance, the antimicrobial potency of blue LED has been demonstrated against several pathogenic bacteria, such as Salmonella spp. [ 176 , 177 ], Listeria monocytogenes [ 176 , 177 , 178 , 179 , 180 ], E. coli [ 181 , 182 ], and bacterial endospores ( Bacillus cereus , B. subtilis , and Clostridium difficile ) [ 183 ]. Generally, the mechanism of blue light sanitization is associated with the absorption of the light by photosensitizers, especially the endogenous porphyrin ( Figure 4 ) [ 35 ], which can result in the generation of ROS [ 184 ].…”
Section: Virucidal Properties Of Blue Lightmentioning
confidence: 99%